Opposite Roles of δ- and μ-Opioid Receptors in BACE1 Regulation and Alzheimer’s Injury - Xu, Yuan; Zhi, Feng; Balboni, Gianfranco; Yang, Yilin; Xia, Ying (Frontiers in Cellular Neuroscience, 2020)
Alzheimer’s disease (AD) is characterized by amyloid plaques and neurofibrillary tangles. Substantial evidence for AD pathogenesis suggests that β-site APP cleaving enzyme 1 (BACE1) and γ-secretase enzyme initiate the amyloidogenic pathway and produces toxic Aβ peptides that prone to aggregate in the brain. Therefore, the inhibition of BACE1 expression and function is an attractive strategy for AD therapy. In the present work, we made the first finding that activating δ-opioid receptors (DOR) with a specific DOR agonist significantly attenuated BACE1 expression and activity in the highly differentiated PC12 cells with mimicked AD injury, while the application of DOR inhibitor naltrindole reversed the UFP-512 effects, and even caused a major increase in BACE1 expression and activity as well as Aβ42 production in physiological conditions. Knocking-down DOR also enhanced BACE1 protein expression and its activity for APP processing, associating with a significant increase in Aβ42 production. In sharp contrast, activation of µ-opioid receptor (MOR) with DAMGO greatly promoted BACE1 expression and activity with an acceleration of APP cleavage, thus contributing to increased Aβ42 production. DADLE, a less selective DOR agonist that may bind to MOR, had no stable inhibitory effect on BACE1. Similar results were also found in APP mutant (APPswe) SH-SY5Y cell line, providing further validation of the DOR action on BACE1 regulation. Our novel data demonstrated entirely different roles of DOR and MOR in the regulation of BACE1 expression and activity with DOR being neuroprotective against AD injury. These findings provided a novel clue for new strategies of AD therapy via targeting endogenous opioid receptors.